Role of secretory clusterin in hepatocarcinogenesis - Yao, Min; Fang, Miao; Zheng, Wenjie; Dong, Zhizhen; Yao, Dengfu (Translational Gastroenterology and Hepatology, 2018)
Secretory clusterin (sCLU) is a small stress-induced cytoprotective chaperone protein. Its biological functions are similar to those of a heat-shock protein. The sCLU plays a crucial role in cell proliferation, multiple drug resistance, metastasis, and tumor progression. Abnormal sCLU expression in tumor tissues or sera of patients with primary hepatic cancer has been considered a useful biomarker for diagnosis and surveillance. However, the exact relationship between sCLU overexpression and malignant transformation of hepatocytes is still unknown. The present review examines some novel advances of the knowledge about the oncogenic role of sCLU in hepatocarcinogenesis.